1984
DOI: 10.1016/s0735-1097(84)80445-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of two-dimensional Doppler echocardiographic techniques for estimating pulmonary to systemic blood flow ratios in children with left to right shunting atrial septal defect, ventricular septal defect or patent ductus arteriosus

Abstract: Range gated two-dimensional Doppler echocardiographic methods were evaluated for quantifying pulmonary (QP) to systemic (QS) blood flow ratios. Twenty-one patients were studied, 4 with patent ductus arteriosus, 6 with atrial septal defect and 11 with ventricular septal defect. The Doppler pulmonary to systemic flow (QP:QS) estimation method involved calculating volume flow (liters/min) at a variety of intracardiac sites by using imaging information for flow area and Doppler outputs to calculate mean flow veloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
2

Year Published

1987
1987
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(13 citation statements)
references
References 14 publications
0
11
0
2
Order By: Relevance
“…[14][15][16][17][18][19]30,[32][33][34][35][36][37][38][39] Recent studies in children, however, have demonstrated that DTI velocities are not only influenced by aging but also more significantly by changes in LV growth parameters, most notably LV end-diastolic dimension and LV mass. 25 Children with congenital heart disease often have distorted ventricular geometry caused by significant alterations in hemodynamic loading conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17][18][19]30,[32][33][34][35][36][37][38][39] Recent studies in children, however, have demonstrated that DTI velocities are not only influenced by aging but also more significantly by changes in LV growth parameters, most notably LV end-diastolic dimension and LV mass. 25 Children with congenital heart disease often have distorted ventricular geometry caused by significant alterations in hemodynamic loading conditions.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33][34] Patients with isolated aortic valve stenosis (AS) comprised a group of patients with increased LV afterload. This group consisted of 96 patients with varying severity of LV outflow obstruction.…”
Section: Study Participantsmentioning
confidence: 99%
“…This can be used clinically to measure blood flow within the heart and great vessels, providing potential not only to determine cardiac output [1][2][3] but also to quantify shunt flow and regurgitant volumes on the basis of flow differences through the individual valves [4] .…”
Section: Introductionmentioning
confidence: 99%
“…1 Two-dimensional (2D) transthoracic echocardiography (TTE) is usually sufficient to assess the anatomy and hemodynamics of a VSD and guide clinical management. 1,2 Recently, percutaneous closure of muscular as well as membranous VSDs using different devices has emerged as an alternative to the surgical technique in selected cases. [3][4][5][6] An accurate assessment of the size and morphology of a VSD is of crucial importance in these cases for device choice.…”
mentioning
confidence: 99%